Evaluating The Prevalence of The Ulcer Pressure in Army’s Soldiers and Evaluating The Practices of Their Companions in Order to Prevent It. (Journal of Hama University, 2020)
The war in Syria has led to various health problems. Among these problems are the injuries of the Syrian Army. These casualties suffer from limitation of movement and loss of sensation noting that their injuries increase and escalate the ulcer pressure. This descriptive study has targeted the prevalence of the ulcer pressure among these casualties and their movement disabilities along with evaluating the practises of the patients’ companions in order to prevent the occurrence and development of ulcer pressure. This is executed by conducting interviews with the companions, which a researcher has developed during 52 visits to patients in their places of staying in Lattakia province. The study concluded that 44.2 % of the patients who participated in the study suffered from the ulcer pressure at the time of the study. In addition, the study concluded that a high percentage of the companions 61.5 % had medium level of experience in preventing the occurring and development of the ulcer pressure. 26.9 % of them had weak level of experience while only 11.5 % had a high level of experience and practice. The Syrian society is in desperate need for such a study and especially after noting new health, social and economic challenges. Our purpose is to highlight the prevalence of this sort of health problems and to prepare a database that would be the starting point in preparing the suitable therapeutic programs that would offer solutions for the health problems of these people, considering what they stand for in regards with the human values and capacities which can assist in the reconstruction process of the country. Based on this study, we should guide the Ministry of Health and the military hospitals to provide home health care through visits that are executed by a team of nursing and medicine specialist in order to fully evaluate each condition and provide appropriate medical and nursing intervention